Peran Lembaga Keuangan Syariah Dalam Mengahadapi Pandemi Covid 19 - Laili, Audra; Noviarita, Heni (ASAS, 2021)
The Covid-19 pandemic has made funding and lending problems even bigger. There is no lending, the withdrawal is also bigger. Thus, BMT's need for funding will be greater, because the need for funds to be withdrawn is also greater. Of course, the liquidity problem of financial institutions including BMT becomes a more serious challenge in the case of Covid-19. In fact, there are several BMTs that can provide financing. Hopefully, this will come. The revolving fund management agency in collaboration with small, medium and micro-medium enterprises (LPDB-KUMKM) has a financing role and comes from banks. The government's role is needed to provide BMT funds, so this BMT will not stop lending. As the growth of Islamic cooperative countries slows down, the global Islamic finance industry is under threat. According to data from SEISRIC, the total number of cases in the Organization of Islamic Cooperation (OIC) countries has reached 180,000.This study used qualitative research methods. This is due to the flexibility in getting information from the latest news stories from trusted sources, regarding how the impact/impact caused by Covid-19 (corona virus), the author also took several news samples from the internet and then combined them into a result. The results are sourced from several news and sources obtained by the author. The author uses an observation technique in the form of observing data related to this Covid-19 (Corona) virus. The results obtained indicate that with the Covid-19 virus pandemic, BMT Amanah Indonesia's financial statements have had an impact on financing achievement, revenue achievement, and operating profit achievement.Keywords: BMT, Islamic Financial Institutions, pandemi virus Covid-19